THE EFFECT OF SERVICE QUALITY ON LOYALTY WITH SATISFACTION AS A MEDIATING VARIABLE - Latjinala, Randy; Adam, Rosida. P.; Mahardiana, Lina (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This study aims to analyze the effect of service quality on customer satisfaction, the impact of service quality on loyalty, and the relationship between customer satisfaction and loyalty at PT Bank Sulteng Palu Branch. The study used explanatory research method to understand the relationship of variables. Respondents were customers of Bank Sulteng Palu Branch, with a sample of 105 people, selected using purposive sampling technique. Data analysis was carried out with descriptive statistics and path analysis using Warp PLS. The results showed that service quality has a significant influence on customer satisfaction, loyalty, and can affect loyalty through customer satisfaction.